Powering up the “biogeochemical engine”: the impact of exceptional ventilation of a deep meromictic lake on the lacustrine redox, nutrient, and methane balances - Lehmann, Moritz F.; Simona, Marco; Wyss, Silvia; Blees, Jan; Frame, Caitlin H.; Niemann, Helge; Veronesi, Mauro; Zopfi, Jakob (Frontiers in Earth Science, 2015)
The Lake Lugano North Basin has been meromictic for several decades, with anoxic waters below 100m depth. Two consecutive cold winters in 2005 and 2006 induced exceptional deep mixing, leading to a transient oxygenation of the whole water column. With the ventilation of deep waters and the oxidation of large quantities of reduced solutes, the lake's total redox-balance turned positive, and the overall hypolimnetic oxygen demand of the lake strongly decreased. The disappearance of 150 t dissolved phosphorous (P) during the first ventilation in March 2005 is attributed to the scavenging of water-column-borne P by newly formed metal oxyhydroxides and the temporary transfer to the sediments. The fixed nitrogen (N) inventory was reduced by 30% ( 1000 t). The water-column turnover induced the nitratation of the previously NO3–free deep hypolimnion by oxidation of large amounts of legacy NH4+ and by mixing with NO3–rich subsurface water masses. Sediments with a strong denitrifying potential, but NO3–starved for decades, were brought in contact with NO3–replete waters, invigorating benthic denitrification and rapid fixed N loss from the lake in spite of the overall more oxygenated conditions. Similarly, a large microbial aerobic CH4 oxidation (MOx) potential in the hypolimnion was capitalized with the ventilation of the deep basin. Almost all CH4, which had been built up over more than 40 years ( 2800 t), was removed from the water column within 30 days. However, boosted MOx could only partly explain the disappearance of the CH4. The dominant fraction (75%) of the CH4 evaded to the atmosphere, through storage flux upon exposure of anoxic CH4-rich water to the atmosphere. As of today, the North Basin seems far from homeostasis regarding its fixed N and CH4 budgets, and the deep basin's CH4 pool is recharging at a net production rate of 66 t y-1. The size of impending CH4 outbursts will depend on the frequency and intensity of exceptional mixing events in the future.